Potensi Lotion Ekstrak Daun Pandan Wangi (Pandanus Amaryllifolius Roxb.) Sebagai Repellent Nyamuk Culex Sp - Farida Mutik Istikomah; Suhartinah Suhartinah; Fitri Kurnia sari (Fakultas Farmasi Universitas Setia Budi, 2024)
Pandan wangi leaves contain flavonoids and have repellent activity. This study uses fragrant pandanus leaves as a substitute for DEET chemicals as repellent for Culex sp Pandan wangi leaves formulated in lotion with concentrations of 4, 8, and 12%. The physical quality of the lotion was observed organoleptically, as well as homogeneity, viscosity, pH, spreadability, stickiness, emulsion type, and cycling test. The test method for repellent effectivity is inserting a proband hand in a cage containing 50 mosquitoes and observing mosquitoes sticking for 5 minutes every hour with a total observation of 6 hours. The results of the repellent effectiveness test and physical quality test on the lotion formulation obtained with a concentration of 4,8 and12% have not shown effective potential results because it still has a repulsion of<80%, the highest protection power result is obtained from the concentration of 12% extract which has a repulsive power of 54.47% the more significant the concentration of the added extract, the greater the protection power produced, But all formulas used have good quality tests.